Traumatic Asphyxia due to Automobile Accident. A Case Report - Elona Markeci; Admir Mustafa (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Traumatic Asphyxia is probably much more common than the surgical literature shows and should always be kept in mind as a possible complication of injuries of the thorax and /or upper abdomen. Traumatic Asphyxia or Perthe’s syndrome is a result of a sudden and severe trauma of the thorax and /or upper abdomen. We report a case of traumatic Asphyxia due to an automobilistic accident.